Evolution of the vertebrate nervous system and telencephalon - Aboitiz, F; Montiel, J (2007)
The first vertebrates (agnathans) were free-living animals with well-developed senses and already had a conspicuous telencephalon receiving a strong and widespread olfactory projection covering large extensions of the pallium, as well as some ventral pallial components such as the septal area and olfactory bulbs. While more basal aspects of the telencephalon may have been associated with the ventral forebrain and were possibly related to motor functions, the more dorsal regions were mainly olfactory but also received dorsal thalamic input from the collothalamic system. Although in hagfishes it is difficult to separate different pallial components (perhaps the central prosencephalic complex relates to the medial pallium, while the rest of the pallium consists of a laterodorsal pallium), in the lamprey it is already possible to separate medial, dorsal, and lateral components of the pallium, as in gnathostomes. In the latter, olfactory projections became largely restricted to the lateral pallium. Interestingly, the medial pallium receives a strong input from the dorsal thalamus, largely conveying sensory information that is relayed in the mesencephalon. This condition persists in most fish, but changes in tetrapods, in which information from lemniscal systems also reach the thalamus and project to the telencephalon. In early gnathostomes, the hemispheres increased in size and may have originally tended to an everted condition in which the medial hemispheres are separated by an extended sheet of choroid plexus. This trend is readily apparent in bony fishes, in which hemispheres become everted. However, cartilaginous fishes developed a prominent dorsal palliumwith an internal nucleus centered at the midline (the central nucleus), thus closing the two hemispheres and generating an evaginated brain. Lungfishes and amphibians are characterized by a juvenilized brain with evaginated hemispheres as well. Amniotes are the first true land vertebrates, as they are able to reproduce on land. Amniotes split very early in two main lineages: stemreptiles, or anapsids, and mammal-like reptiles, or pelycosaurs. These early animals had very simple brains, which were possibly similar to those of present-day amphibians, where olfactory input reaches the lateral and the dorsal pallium, while dorsal thalamic projections reach the medial pallium. Reptiles develop a small cortex, consisting of medial, dorsomedial, dorsal, and lateral fields, plus a large periventricular structure termed the dorsal ventricular ridge, receiving most collothalamic input. Lemnothalamic inputs are sent mostly to the dorsal cortex. Mammals develop a large, six-layered neocortex that is topographically equivalent to the reptilian dorsal cortex and receives both lemnothalamic and collothalamic inputs.